The Influence of Consumer Satisfaction Mediating Price on Consumer Loyalty in Shopping at J.Co Donuts in Denpasar - Ni Made Dwi Handayani; I Gede Adi Setiawan (PT. Global World Scientific, 2025)
This study aims to analyze the effect of price on consumer loyalty with satisfaction as a mediating variable for J.Co Donuts consumers in Denpasar. The increasingly competitive culinary business competition requires companies to be able to determine a pricing strategy that not only reflects value, but also builds sustainable customer satisfaction. The research method uses a quantitative approach with path analysis techniques, involving 30 respondents selected by purposive sampling. Data were collected through questionnaires covering price, satisfaction, and loyalty variables, then analyzed using regression tests. The results showed that price has a significant effect on customer satisfaction, but the effect of price on loyalty, both directly and indirectly through satisfaction, is not significant. Furthermore, the analysis shows that customer satisfaction does not act as an effective mediator in the relationship between price and loyalty. The indirect effect of price on loyalty through satisfaction is only 0.0147, a very small and insignificant value. This confirms that consumer loyalty is not solely formed by perceived price or satisfaction, but by other factors such as service quality, product innovation, and brand image. Thus, this study implies that companies need to combine price strategies with other marketing aspects to build stronger loyalty. This research also provides an academic contribution regarding the importance of understanding the limited mediating role of satisfaction in shaping consumer loyalty.